Pengaruh Pendapatan Asli Daerah, Dana Alokasi Khusus, Dana Alokasi Umum, Total Aset Dan Luas Wilayah, Terhadap Belanja Modal Economic Growth Sebagai Variabel Moderating Provinsi Di Indonesia Tahun 2014-2016. - Widiasmara, Anny (IAIN Surakarta, 2019)
The research aims to empirically examine the effect of regional original income, general allocation funds, special allocation funds, total assets, total area, and economic growth as moderating variables on capital expenditures in provinces in Indonesia in 2014-2016. The data is obtained from www.bps.go.id annual financial report. The analytical tool used in this study is Modereted Regression Analysis. The results of this study variables that have a significant effect are Special Allocation Funds, and Total Assets to Capital Expenditures. Whereas the Original Regional Opinion, General Allocation Funds, and Area Size have no effect on Capital Expenditures. Economic growth variable moderates the relationship between DAU and TA to Capital ExpendituresKeywords: Capital Expenditures, PAD, DAU, DAK, Total assets, Area, Economic growth